Do Social Protection Transfers Reduce Poverty and Vulnerability to Poverty in Pakistan? Household Level Evidence from Punjab. Issue 8 (3rd August 2019) - Azeem, Muhammad Masood; Mugera, Amin W.; Schilizzi, Steven
Abstract: Empirical studies in different developing countries have investigated the impact of social protection (SP) on ex-post poverty; however, few studies analysed the impact of SP on ex-ante vulnerability to poverty (VtP). This paper contributes to the literature by evaluating the impact of SP on vulnerability to poverty (VtP) and poverty rates among households in the Punjab province of Pakistan. A hierarchical modelling approach is used to analyse the Multiple Indicator Cluster Survey (MICS-2011) data of about 90, 000 households. Matching methods and simultaneous endogenous switching regression are used to control for potential selection bias and estimate average treatment effects. Our results show that SP has a positive impact in reducing household poverty and VtP, but this impact is mainly driven by a short-term flood relief cash transfer programme, pension of government employees and households' regular purchase from utility store network.